GAMBARAN MASALAH PEMBERIAN ASI PADA IBU DI WILAYAH KERJA PUSKESMAS PALMATAK - Bambang Ari Purwoko; Oswati Hasanah; Herlina Herlina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
One of the efforts that can be done to reduce the infant mortality rate is by giving breast milk exclusively. Exclusive breastfeeding is breast milk that is given to babies, without adding and / or replacing with other food or drinks (except drugs, vitamins, and minerals). Children who are not sufficiently breastfed will be disrupted in their growth and development process and will be more prone to experiencing health problems in the future. The low rate of exclusive breastfeeding for infants is caused by problems in the mother. This study aims to analyze the description of problems in breastfeeding Palmatak Health Center with a descriptive research design with cross sectional approach. The sample of this research was 67 respondents taken using total sampling technique. The results showed the majority of research subjects were mothers aged 26-35 years (67.2%), the latest education was mothers of universities (35.8%), occupations of IRT mothers (55.2%),Malay ethnic (91.0%), gender of male respondents (59.7%), babies over 6 months (50.7%). The results of this study also show that the majority of mothers experience breast milk problems (65.7%). Breastfeeding problems are most common when babies are 0-4 months old (56.7%). It is expected that the primary health center can be made a reference for counseling material on breastfeeding problems for mothers.Keywords: breastfeeding, mother, problems